The Nature of the Regional Representative Council's Supervisory Function on the Implementation of the Regional Revenue and Expenditure Budget - Jawad, Abdul; Hidjaz, Kamal; Bima, Muhammad Rinaldy; Badaru, Baharuddin (Journal of Cultural Analysis and Social Change, 2026)
This study aims to examine and explain the nature, forms, and determining factors of the oversight function exercised by the Regional People’s Representative Council (DPRD) over the implementation of the Regional Revenue and Expenditure Budget (APBD) in East Kalimantan Province. Specifically, the research analyzes how DPRD supervision is conducted, to what extent it aligns with the mandate of the prevailing legal framework, and what institutional, political, and administrative factors influence its effectiveness. The study employs a combined normative and empirical legal research approach, using qualitative methods. Normative analysis is applied to examine statutory provisions, particularly Law Number 23 of 2014 on Regional Government, while empirical data are obtained through interviews, observations, and document analysis to capture practices and dynamics in the field. The findings reveal that, in principle, the DPRD is granted legislative, budgeting, and supervisory functions, positioning it as a key political oversight institution alongside the regional executive. DPRD also holds interpellation, inquiry, and opinion rights, enabling it to correct policy deviations. However, DPRD oversight of the APBD in East Kalimantan has not operated optimally. Constraining factors include limited capacity and competence of council members, restricted transparency and data access, political dynamics in executive–legislative relations, inadequate facilities and institutional support, as well as issues of ethics and political integrity. Strengthening DPRD’s code of ethics, enhancing internal control by the Ethics Council, and fostering constructive partnerships with the executive are recommended to improve accountability and good governance in regional financial management.